Diskursus Kebersamaa Umat sebagai Wujud Hidup Menggereja - Munatar Kause; Yudhi Kawangung; Desi Arisandi Laga Nguru; Vera Herawati Siahaan; Elias Modok (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
As socialized by the former Minister of Religion of the Republic of Indonesia Lukman Hakim, that there are three mantras that will become the flagship program of the Ministry of Religion of the Republic of Indonesia, namely: Religious Moderation; Togetherness of the People; and Data Integration. Three major schemes are the main focus in moving the national development curve in the field of religious level and religious education. It is inevitable that the Indonesian nation is often hit by the issue of religious intolerance in some regions, so that it is quite draining of thought and energy and leaves a humanitarian issue that is alienated from a society that is far from harmonizing with diversity. This article aims to offer and at the same time present a breakthrough in the awareness of the mind that is surrounded by the clogged public space, in this case the isolation of social structures so that there is friction, so a simple conception is needed to unravel this. The togetherness of the people is an important key in releasing the shackles of division (segmentation) and separation (fragmentation) among the people, so that this attachment is a new form of church life. The approach method used is qualitative literature which is thoroughly explored to find the meaning behind the phenomenon.